High-Density SNP Map Construction and QTL Identification for the Apetalous Character in Brassica napus L. - Wang, Xiaodong; Yu, Kunjiang; Li, Hongge; Peng, Qi; Chen, Feng; Zhang, Wei; Chen, Song; Hu, Maolong; Zhang, Jiefu (Frontiers in Plant Science, 2015)
The apetalous genotype is a morphological ideotype for increasing seed yield and should be of considerable agricultural use; however, only a few studies have focused on the genetic control of this trait in Brassica napus. In the present study, a recombinant inbred line, the AH population, containing 189 individuals was derived from a cross between an apetalous line ‘APL01’ and a normally petalled variety ‘Holly’. The Brassica 60 K Infinium BeadChip Array harboring 52,157 single nucleotide polymorphism (SNP) markers was used to genotype the AH individuals. A high-density genetic linkage map was constructed based on 2,755 bins involving 11,458 SNPs and 57 simple sequence repeats, and was used to identify loci associated with petalous degree (PDgr). The linkage map covered 2,027.53 cM, with an average marker interval of 0.72 cM. The AH map had good collinearity with the B. napus reference genome, indicating its high quality and accuracy. After phenotypic analyses across five different experiments, a total of 19 identified quantitative trait loci (QTLs) distributed across chromosomes A3, A5, A6, A9 and C8 were obtained, and these QTLs were further integrated into nine consensus QTLs by a meta-analysis. Interestingly, the major QTL qPD.C8-2 was consistently detected in all five experiments, and qPD.A9-2 and qPD.C8-3 were stably expressed in four experiments. Comparative mapping between the AH map and the B. napus reference genome suggested that there were 328 genes underlying the confidence intervals of the three steady QTLs. Based on the Gene Ontology assignments of 52 genes to the regulation of floral development in published studies, 146 genes were considered as potential candidate genes for PDgr. The current study carried out a QTL analysis for PDgr using a high-density SNP map in B. napus, providing novel targets for improving seed yield. These results advanced our understanding of the genetic control of PDgr regulation in B. napus.